Comparative Plastid Genomics of Neotropical Bulbophyllum (Orchidaceae; Epidendroideae) - Zavala-Páez, Michelle; Vieira, Leila do Nascimento; Baura, Valter Antônio de; Balsanelli, Eduardo; Souza, Emanuel Maltempi de; Cevallos, Marco Cerna; Chase, Mark W.; Smidt, Eric de Camargo (Frontiers in Plant Science, 2020)
Pantropical Bulbophyllum, with ca. 2,200 species, is one of the largest genera in Orchidaceae. Although phylogenetics and taxonomy of the c. 60 American species in the genus are generally well understood, some species complexes need more study to clearly delimit their component species and provide information about their evolutionary history. Previous research has suggested that the plastid genome includes phylogenetic markers capable of providing resolution at low taxonomic levels, and thus it could be an effective tool if these divergent regions can be identified. In this study, we sequenced the complete plastid genome of eight Bulbophyllum species, representing five of six Neotropical taxonomic sections. All plastomes conserve the typical quadripartite structure, and, although the general structure of plastid genomes is conserved, differences in ndh-gene composition and total length were detected. Total length was determined by contraction and expansion of the small single-copy region, a result of an independent loss of the seven ndh genes. Selection analyses indicated that protein-coding genes were generally well conserved, but in four genes, we identified 95 putative sites under positive selection. Furthermore, a total of 54 polymorphic simple sequence repeats (SSRs) were identified, for which we developed amplification primers. In addition, we propose ten regions with potential to improve phylogenetic analyses of Neotropical Bulbophyllum species.